Mediasi Trust Dalam Mempengaruhi Pemasaran Media Sosial Terhadap Niat Beli Konsumen (Studi Konsumen Muna Beauty Store) - Rohma, Maulidya; Suyono, Suyono (Management Department of Economics and Business Of Trunojoyo Madura University, 2024)
This study aims to determine Trust mediation in influencing Social Media Marketing on consumer purchase intentions (study on Muna Beauty Store consumers). The method used in this research is purposive sampling, namely the technique of determining the sample by considering certain criteria with a total sample of 96 respondents. With multiple linear regression and analysis method. The results of this study indicate that 1) Social Media Marketing has a positive and significant direct effect on Trust at Muna Beauty Store. 2) Social Media Marketing has a direct significant positive effect on Consumer Purchase Intentions at Muna Beauty Store. 3) Trust has a significant positive direct effect on the Purchase Intention of Muna Beauty Store Consumers. 4) Social Media Marketing indirectly has a positive and significant effect on Consumer Purchase Intentions through Trust.